Mycorrhizal associations modify tree diversity−productivity relationships across experimental tree plantations - Luo, S; Schmid, B; Hector, A; Scherer‐Lorenzen, M; Verheyen, K; Barsoum, N; Bauhus, J; Beyer, F; Bruelheide, H; Ferlian, O; Godbold, D; Hall, JS; et al. (Wiley, 2024)
Summary: Decades of studies have demonstrated links between biodiversity and ecosystem functioning, yet the generality of the relationships and the underlying mechanisms remain unclear, especially for forest ecosystems. Using 11 tree‐diversity experiments, we tested tree species richness–community productivity relationships and the role of arbuscular (AM) or ectomycorrhizal (ECM) fungal‐associated tree species in these relationships. Tree species richness had a positive effect on community productivity across experiments, modified by the diversity of tree mycorrhizal associations. In communities with both AM and ECM trees, species richness showed positive effects on community productivity, which could have resulted from complementarity between AM and ECM trees. Moreover, both AM and ECM trees were more productive in mixed communities with both AM and ECM trees than in communities assembled by their own mycorrhizal type of trees. In communities containing only ECM trees, species richness had a significant positive effect on productivity, whereas species richness did not show any significant effects on productivity in communities containing only AM trees. Our study provides novel explanations for variations in diversity–productivity relationships by suggesting that tree–mycorrhiza interactions can shape productivity in mixed‐species forest ecosystems.